Strategi Komunikasi Badan Narkotika Nasional Provinsi DKI Jakarta Dalam Upaya Pencegahan Penyalahgunaan Narkoba di Kalangan Remaja - Yughni Sabira, Almira; Widowati Herieningsih, Sri (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
DKI Jakarta has been one of the provinces with the highest prevalence of using drugs in 2016. The DKI Jakarta National Narcotics Agency as an institution for the prevention and eradication of drugs at the DKI Jakarta Provincial level has a very important role. A good strategy is needed in handling drug problems by the BNNP DKI Jakarta, one of which is the Communication Strategy, especially efforts to prevent abuse among teenagers. This type of research is descriptive qualitative research using techniques of data reduction analysis, data presentation, and conclusion drawing. The results of this study indicate that the BNNP DKI Jakarta carries out a similar pattern of strategy every year. The strategy is carried out through two programs, namely Information Dissemination dan advocacy. Through this strategy, BNNP DKI Jakarta is trying to improve the resilience or responsiveness of high school teenagers to the prevention of drug abuse as indicated by various activities and active participation in prevention. All of programs supported by several types of media as a medium for Disseminating Information, both about the types of drugs and the dangers of drug abuse. The strategy is carried out through two programs, namely Information Dissemination and Advocacy. The two programs were implemented at the target High School Teenagers in several locations, but there were two regions that were not yet available at the City level BNN, namely West Jakarta and Central Jakarta, so it was of particular concern to the BNNP DKI Jakarta in implementing the Program